2021
DOI: 10.1038/s41419-020-03344-6
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new molecule inducing melanoma cell death: dual AMPK/MELK targeting for novel melanoma therapies

Abstract: In the search of biguanide-derived molecules against melanoma, we have discovered and developed a series of bioactive products and identified the promising new compound CRO15. This molecule exerted anti-melanoma effects on cells lines and cells isolated from patients including the ones derived from tumors resistant to BRAF inhibitors. Moreover, CRO15 was able to decrease viability of cells lines from a broad range of cancer types. This compound acts by two distinct mechanisms. First by activating the AMPK path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The results obtained, both in vitro and in vivo, showed tha CRO15 induces autophagy by accumulating LC3 in melanoma cancer cells. Moreover, the performed in vivo studies did not show strong toxicity of the tested compound in mice All of this data suggests that CRO15 should be further evaluated as a potential anticancer drug [223].…”
Section: Autophagy Activator Chemical Structure Preclinical Studies Referencesmentioning
confidence: 74%
See 1 more Smart Citation
“…The results obtained, both in vitro and in vivo, showed tha CRO15 induces autophagy by accumulating LC3 in melanoma cancer cells. Moreover, the performed in vivo studies did not show strong toxicity of the tested compound in mice All of this data suggests that CRO15 should be further evaluated as a potential anticancer drug [223].…”
Section: Autophagy Activator Chemical Structure Preclinical Studies Referencesmentioning
confidence: 74%
“…Moreover, the performed in vivo studies did not show strong toxicity of the tested compound in mice. All of this data suggests that CRO15 should be further evaluated as a potential anticancer drug [ 223 ].…”
Section: Autophagy Inhibitors and Activatorsmentioning
confidence: 99%
“…Interestingly, many of the co-crystallized MELK inhibitors, as well as our inhibitor series, exhibit binding modes with only one hydrogen bond acceptor acting as an anchoring group toward the hinge region, instead of the 3-point donor-acceptor-donor motif that is typical for other kinases. [33] The eight follow-up compounds represent two subclasses: (i) compounds 9-12 contain pyridyl rings in place of the 2phenyl unit, enabling us to explore the effect of an H-bond accepting heteroatom in either position of this ring, while (ii) compounds 15-18 contain an ethyl group in position 10, with chloro substituents in varying positions of the 2-phenyl unit (15)(16)(17), or a methoxy group in the 4 position (18).…”
Section: Resultsmentioning
confidence: 99%
“…[14,15] Juane and coworkers found that the biguanide-derived compound CRO15 targets both MELK and AMPK, which can be an effective way for novel melanoma therapies. [16] Wang et al designed and synthesized 1H-pyrrolo [2,3-b]pyridine derivatives as potential inhibitors of MELK and they have found a compound with an IC 50 of 32 nM against MELK. [17] While earlier virtual screening efforts relied on homology modeling, [18] currently 31 crystal structures of MELK (homo sapiens) are available in the PDB database [19,20] for structure-based virtual screening efforts toward new inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation